OVERCOME MENOPAUSE SYMPTOMS WITH YOGA THERAPY - MRS.PAPPY YUVARANI (International Journal of Pharma and Bio Sciences, 2016)
Menopause is a natural biological process although it ends fertility you can stay healthy , vital and sexual ,some women feel relived no longer to worry about pregnancy. even though some physical symptoms such as hot flashes and emotional disturbances of menopause may interrupt your sleep and low your energy levels. Specific treatment is not needed, but some symptoms may get improved with specific treatment Menopause does not really require medical treatment since it is a natural biological process. The Menopause treatments actually focus on relieving the symptoms of Menopause and in preventing any chronic condition that may occur during the postmenopausal years such as heart disease and osteoporosis. Some undergo Hormonal Replacement Therapy (HRT) which provides a low dose of estrogen in the body which helps in alleviating symptoms such as hot flashes and vaginal dryness. HRT may also combine progestin with estrogen. Women who had hysterectomy only take Estrogen Replacement Therapy (ERT), which is HRT using estrogen alone. HRT, however, has some serious side effects and increases your risk to heart problems. Exercising, proper diet, not smoking, and reduction of stress are also effective ways to make Menopause more bearable and can also facilitate in preventing any chronic ailments that can occur in the postmenopausal years Some basic yoga practices can help one go through these symptoms with ease and comfort. These practices elevates your mood, fills you with positive high prana and makes the body strong enough to bear with the changes it’s going through.